Papua New Guinea High Frequency Phone Survey on COVID-19 : Data Collection - May-July 2021 - United Nations; UNICEF; World Bank (Washington, DC: World Bank, 2022)
This joint report by the World Bank and UNICEF-PNG presents the findings from two mobile phone surveys conducted in May, June and July 2021 in Papua New Guinea. The first survey, conducted in May and June, was the third in a series, with the first round being completed in June and July 2020 and the second round being conducted in December 2020. This survey interviewed a total of 2,533 respondents about the impact of COVID-19 on their economic activity and the results were weighted using information from the 2016–2018 Demographic and Health Survey (DHS) to reflect nationally representative estimates of the socioeconomic impacts of COVID-19. The second survey, conducted in June and July 2021, interviewed a total of 2,541 respondents (1880 of whom were from the first survey) about the impact of COVID-19 on a range of areas that broadly can be considered human development. These results were also weighted using information from the DHS to develop representative estimates. The report uses data that predates the arrival of the Delta variant of COVID-19 in PNG and therefore should be considered a snapshot of changes in economic activity and human development from January to June 2021. The next round of data collection is currently planned to start in November 2021 and thatsurvey will shed light on the impact of the Delta variant of COVID-19 in PNG. The surveys in this report show that in general there were similar levels of economic activity and human development in mid-2021 as the start of 2021, however the surveys do not demonstrate a recovery to pre-pandemic levels. There was stabilization across a range of indicators, including levels of employment, access to education and healthcare as well as public trust and security. However, there was some variation across regions and wealth quintiles. The lack of deterioration of conditions since the start of 2021 is notable given that over this period there was a rapid escalationof the COVID-19 crisis in March followed by a fall in COVID-19 cases throughout May.